Pengembangan Leaflet Pencegahan dan Pengendalian Overweight Sebagai Media Penyuluhan dalam Meningkatkan Pengetahuan - Al Rahmad, Agus Hendra; Salsabila, Jeumpa Syahrana; Erwandi, Erwandi; Fadjri, T. Khairul (Poltekkes Kemenkes Jambi, 2024)
Background: A 2016 WHO report showed that over 340 million children and adolescents aged 5-19 years are obese. From 2000 to 2017, 38.3 million children worldwide were obese. This changed from 4.9% in 2000 to 5.6% in 2017 and more than 2 million children in Indonesia are overweight or obese. Methods: This type of research is quantitative, using a quasi-experimental design (pseudo-experiment) with a pretest and posttest design. The subjects were 35 female students of Al-Fityan IT High School. The research location will be implemented in Al-Fityan IT High School with a research plan in May 2023. Data collection included primary and secondary data that were processed through editing, coding, scoring, processing, and cleaning stages. Data analysis was performed using R-statistical software, including the T-dependent test with a 95% confidence level (α = 0.05). Results: The research data will be presented in tabular and textual form. Results: The mean knowledge of students before education was lower (12.42) than that after education (15.02). Statistical results showed that counseling using leaflets had an effect on changes in knowledge of overweight (p=0.000). Conclusion: Education through counseling using leaflet media on the prevention and control of overweight has an effect on increasing the knowledge of adolescents at IT Al-Fityan High School in Aceh Besar. Keywords: Overwewight Prevention, Overweight, Leaflet